Atmospheric Lamb wave pulse and volcanic explosivity index following the 2022 Hunga Tonga (South Pacific) eruption - Dalal, Prohelika; Kundu, Bhaskar; Panda, Jagabandhu; Jin, Shuanggen (Frontiers in Earth Science, 2023)
Atmospheric Lamb wave induced by the Hunga-Tonga volcanic eruption on 15th January 2022 is recorded as atmospheric pressure fluctuations at various meteorological stations around the globe, persisting for several days even after the eruption. This wave has not been reported from any large eruption in the last few decades. In the present study, the barometric pressure change data is used as a proxy to determine the Volcanic Explosivity Index (VEI) of this eruption. An empirical equation is used as a function of the size of the eruption and the distance of the barometric station from the source of eruption (or explosion) epicenter, which determines the volume of eruption to be ~8.6 km3 from pressure change data. Accordingly, the VEI of the eruption is found to be 5. The Lamb wave derive VEI is consistent with the seismological estimates and hence can be considered as a first-order parameter of the volcanic eruption.